Penerapan Metode Diskusi-Demonstrasi dalam Pembelajaran Seni Budaya (Tari) di SMAN 1 Kuantan Mudik - Ru’ya Shaputri; Susmiarti Susmiarti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research is motivated by the low learning outcomes of cultural arts. The reason is that the use of the learning model and students' understanding of learning is not optimal. The purpose of this study is to describe the improvement of cultural arts learning outcomes by using the Discussion-Demonstration method in class XI.1 of SMA Negeri 1 Kuantan Mudik. This research is a Class Action Research (PTK) that uses qualitative and quantitative approaches. It is carried out in two cycles, namely cycle I consists of 2 meetings and cycle II consists of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation and reflection. The subjects of this study are teachers and students of class XI.1 of SMA Negeri 1 Kuantan Mudik with a total of 36 people. The results of the study showed an increase in: a) the implementation in the aspect of teachers in the first cycle of meeting 1 with an average of 3.06 with good criteria, the first cycle of meeting 2 with an average of 3.41 with good criteria and the second cycle of 3.93 (very good), while in the aspect of students in the first cycle of meeting 1 with an average of 1.87 (not good), the first cycle of meeting 2 with an average of 3.31 (good) and the second cycle of 3.87 (very good), b) Assessment of student learning outcomes in cycle I with an average score of 66 and cycle II with an average score of 90. Based on these results, it can be concluded that using the Discussion-Demonstration Method can improve the learning outcomes of cultural arts in class XI.1 students of SMA Negeri 1 Kuantan Mudik.